2023
DOI: 10.1002/ccr3.7548
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of exercise and essential amino acid plus cholecalciferol supplementation on physical fitness and body composition in multiple sclerosis: A case study

Abstract: In MS patients, especially those frail or malnourished, combining home-based exercise twice weekly with essential amino acids and vitamin D may improve body composition, strength, and physical performance, enabling long-term functional improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…The intervention included exercise interventions twice a week and the administration of dietary supplements containing 7.5 g of essential amino acids and 500 IU of cholecalciferol twice a day. 133 At week 24, the total lean body mass of the patient increased by 1.0%, and the lean body mass of the arms and legs increased by 6.9% and 6.3%, respectively. In a cross-sectional study, Rivadeneyra et al found that female Parkinson’s patients with low physical activity and low energy intake were more likely to develop sarcopenia.…”
Section: Combining Exercise With Dietary Supplementsmentioning
confidence: 92%
“…The intervention included exercise interventions twice a week and the administration of dietary supplements containing 7.5 g of essential amino acids and 500 IU of cholecalciferol twice a day. 133 At week 24, the total lean body mass of the patient increased by 1.0%, and the lean body mass of the arms and legs increased by 6.9% and 6.3%, respectively. In a cross-sectional study, Rivadeneyra et al found that female Parkinson’s patients with low physical activity and low energy intake were more likely to develop sarcopenia.…”
Section: Combining Exercise With Dietary Supplementsmentioning
confidence: 92%
“…Among these, home exercise, swimming, aerobic exercise, and resistance exercise, as well as a variety of combined exercise training programs, can improve glucose tolerance and reduce blood sugar levels and insulin resistance. Varying degrees of improvement have also been observed ( Patyn, 2014 ; Wens et al, 2015 ; Sadegh and Golestany, 2017 ; Wens et al, 2017 ; Ispoglou et al, 2023 ).…”
Section: Exercise Reduces Insulin Resistance and Improves Neurologica...mentioning
confidence: 97%